Body composition and environmental factors’ influence on metabolically unhealthy obesity in children: insights from the CCACH study - Xie, Xiangjun; Cheng, Hong; Xiong, Jingfan; Li, Yan; Xiao, Pei; Dong, Hongbo; Shan, Xinying; Li, Yanyan; Fu, Liwan; Mi, Jie (Frontiers in Nutrition, 2025)
BackgroundMetabolically unhealthy obesity (MUO) is a subtype of obesity characterized by alterations in metabolic health parameters, such as elevated glycemia, dyslipidemia, and increased blood pressure. Body composition, lifestyle behaviors, and their interactions influence its development. This study examined the impact of body composition and lifestyle factors on MUO phenotypes in children and adolescents with obesity.MethodsThe study included 1,375 children with obesity, aged 6–19 years, from China. All participants underwent dual-energy X-ray absorptiometry (DXA) for the evaluation of body composition. Participants were classified as having MUO based on either insulin resistance (IR) or cardiometabolic risk (CR) factors (blood pressure, lipids, and glucose). The study also assessed the influence of body composition in conjunction with environmental factors, including lifestyle aspects and family medical history.ResultsThe prevalence of MUO-CR and MUO-IR was 43.6 and 38.9%, respectively. Android fat mass (FM), visceral fat, and fat-free mass (FFM) were identified as significant independent predictors of MUO, regardless of the CR or IR definitions used. For MUO-CR, a significant interaction was found between fast food consumption, FM, and FFM. For MUO-IR, sleep duration exhibited a notable interaction with FFM and FM across different regions. No comparable effect was observed for physical activity.ConclusionThis study suggests that the prevalence of MUO is below 50% in Chinese children with obesity. The results reveal that body composition and lifestyle factors are significantly linked to MUO status.